Participação do sistema colinérgico na inflamação e no comportamento doentio em animais deficientes para o transportador vesicular de acetilcolina (VAChT) - Hercules Ribeiro Leite (2013)
The production of inflammatory mediators is necessary to protect the body against pathogens and promote tissue repair, but the excessive release of cytokines can lead to systemic inflammation, neuroinflammation and "sickness behavior". The central nervous system dynamically interacts with the immune system to modulate the inflammatory process through humoral and neural pathways. In this context has been discussed the "cholinergic anti-inflammatory" pathway able to inhibiting cytokine production, since signals transmitted through the vagus nerve converge to immune system cells that express the alpha 7 nicotinic cholinergic receptor (7 nAChR), preventing the release of pro-inflammatory mediators. Prado et al developed an animal model of central and peripheral cholinergic hypofunction, where the gene of vesicular acetylcholine transporter (VAChT) has his expression decreased in 45% of the protein VAChT. In this context, cholinergic balance adjustment appears to be closely involved with the generation and progression of the inflammatory process. Thus, changes in cholinergic tone could increase susceptibility to inflammatory lesions, both systemic and in the central nervous system. Thus, this study aimed to characterize the systemic and cerebral inflammatory process, neuronal activity in brainstem and its implications in the generation of "sickness behavior" after administration of LPS in homozygous mice deficient for VAChT (VAChT KDHOM). For this purpose, male mice were divided into groups: saline (SAL WT or VAChT KDHOM SAL) or animals treated with lipopolysaccharide (LPS) (LPS WT or VAChT KDHOM LPS), as well as animals that received administration of acetylcholinesterase inhibitor (ACEI) (WT LPS ACEI or VAChT KDHOM LPS ACEI) or nicotine agonist (NIC) (WT LPS NIC or LPS VAChT KDHOM NIC). Initially, animals were given a lethal dose of LPS i.p (10 mg/kg) to evaluate survival rate. Subsequently, we administered sublethal dose of LPS (0.1 mg/kg) in order to adequately control the parameters to be evaluated, inflammatory markers and sickness behavior. To assess the reversal of the phenotype, animals were prior administered with pyridostigmine (3 mg/kg) or nicotine (0.4 mg/kg). Animals were sacrificed 1 or 3 h after administration of sublethal dose of LPS i.p. The results showed a lower survival of animals VAChT KDHOM after administration of a lethal dose of LPS. In addition, systemic inflammation showed an increase in splenic proinflammatory (TNF, IL-1, IL-6) and anti-inflammatory (IL-10) status in the VAChT KDHOM LPS. Concomitantly, was observed an increased activity of splenic macrophages, as well as an increased recruitment of lymphoid follicles in the same organ, indicating that the cholinergic deficit was able to alter the inflammatory balance. The serum profile was altered in VAChT KDHOM LPS group, where mediators TNF and IL-6 were elevated, however without changing blood and peritoneal leukocytes levels. The reversal of phenotype by ACEI showed to be effective only in reducing the TNF levels of serum and spleen. However, the nicotinic agonist reduced almost totally the inflammatory mediators in serum and spleen. Interestingly, it was demonstrated an increased neuronal activity through c-Fos gene in the nuclei of the dorsal vagal complex in animals VAChT KDHOM LPS (Postrema Area PA, Nucleus of the Solitary Tract - NST, and Dorsal Motor Nucleus - DMN), responsible for modulating afferent sensory and motor efferent vagal cholinergic anti-inflammatory pathway. An increased vagal activity in those nuclei would be the a gateway to the modulation of neuroinflammation found in the present study, where we showed an increased of TNF, IL-1, IL-6 and IL-10 levels reversed 100% by nicotinic agonist in mice deficient for the VAChT. Both humoral and neuronal mechanisms are related to the onset of sickness behavior in situations of systemic inflammation and neuroinflammation. Thus, in our study we found that the spectrum of abnormalities could positively influenced the thermoregulatory changes, as well as depressive profile, and reduced exploratory activity and general spontaneous locomotor activity in VAChT KDHOM animals treated with endotoxin LPS. Our results also demonstrate for the first time evidences that the decreased expression of VAChT is able to alter the inflammatory balance against the invasion of pathogens, leading to systemic and brain inflammatory changes, thermoregulation, besides behavioral deficits.